Development Career Generation Z In Human Resource Management Perspective In The Digital Era - Angelica Cindy; Anggi Putri Anisyah; Dea Nadya; Ira Amalia; Tarisa Oktafia Devi; Vini Deva Agustini; Ely Delvi (Yayasan Multidimensi Kreatif, 2024)
This study discusses the role of career development of generation z in the perspective of human resource management in the digital era. The importance of human resource management (HR) is becoming increasingly fundamental along with the rapid development of technology and changes in workforce needs. The purpose of this study is to determine the strategy for managing human resources (HR). man For fulfil challenge And opportunity Which faced by Generation Z, with a focus on career development and to identify key factors in implementation strategy management source Power man Which effective in Generation Z, which can make a positive contribution to career development. In the study “Generation Z Career Development in the Perspective of Human Resource Management”, a qualitative approach can be a very relevant method and provide an in-depth understanding of Gen Z career development in the perspective of human resource management, challenge Generation Z, And improvement maturity career. Results research is that personalization of career development plans is an effective strategy to meet the needs of Generation Z individuals, given their preference for recognition of each individual's uniqueness. Through this personalization, organizations can build stronger bonds with employees and create more meaningful experiences.